Conserved interferon-γ signaling drives clinical response to immune checkpoint blockade therapy in melanoma - Grasso, Catherine S. (Cancer Cell, 2020)
SUMMARY: We analyze the transcriptome of baseline and on-therapy tumor biopsies from 101 patients with advanced melanoma treated with nivolumab (anti-PD-1) alone or combined with ipilimumab (anti-CTLA-4). We find that T cell infiltration and interferon-γ (IFNγ) signaling signatures correspond most highly with clinical response to therapy, with a reciprocal decrease in cell cycle and WNT signaling pathways in responding biopsies. We model the interaction in 58 human cell lines, where IFNγ in vitro exposure leads to a conserved transcriptome response unless cells have IFNγ receptor alterations. This conserved IFNγ transcriptome response in melanoma cells serves to amplify the antitumor immune response. Therefore, the magnitude of the antitumor T cell response and the corresponding downstream IFNγ signaling are the main drivers of clinical response or resistance to immune checkpoint blockade therapy. ETOC BLURB: Analyzing the transcriptome of biopsies of patients during immune checkpoint blockade therapy, Grasso et al. show that the increase of T cell infiltration and the downstream IFNγ signaling drive clinical responses.